Impact of pre-service teachers’ self-regulation and self-efficacy on their mathematics performance in blended learning - Peteros, Emerson D. (Journal of Education and Learning (EduLearn), 2024)
This research investigated the pre-service teachers’ self-regulation, self-efficacy, and mathematics performance in blended learning during the post Coronavirus disease 2019 (COVID-19) pandemic in a state university using a descriptive correlational design. There were 201 pre-service teachers who were identified using simple random sampling. They answered the two-set survey questionnaire, which assessed their self-regulation and self-efficacy, while their performances were assessed using their grades in the subject. The data gathered were treated using descriptive and inferential statistics. The results revealed that they had high self-regulation while they had a very high level of self-efficacy. At the same time, they had a very satisfactory performance in mathematics. Moreover, their self-regulation in terms of planning, monitoring, and adjusting was significantly correlated with their math performance while reflecting is not. However, no significant relationship was found between their self-efficacy and mathematics performance. Thus, instructors are encouraged to conduct monitoring during blended learning to encourage pre-service teachers to maintain their high level of self-regulation and self-efficacy in learning mathematics. In addition, future researchers may explore the same variables to validate the findings of the study because these findings are limited only to pre-service teachers and were conducted during the post COVID-19 pandemic.